PENANGGULANGAN KERUSAKAN LINGKUNGAN OLEH DINAS LINGKUNGAN HIDUP AKIBAT TAMBANG ILEGAL DI KABUPATEN LUWU DI DESA KADUNDUNG - Darlis, Darlis; Hartono; Haryanto, Wawan (Datuk Sulaiman Law Review (DaLRev), 2025)
The role of the Luwu Regency Environmental Service in efforts to control environmental damage due to illegal mining in Kadundung Village, Latimojong District. Aims to determine the role of the Luwu Regency Environmental Service in controlling environmental damage due to illegal mining in Kadundung Village, Latimojong District. and factors that hinder controlling environmental damage in Kadundung Village, Katimojong District, Luwu Regency. The type of research used in this research is the Empirical Legal Method with a Case and Law Approach. And the data sources for this research are sources, primary data, secondary data sources and tertiary data sources and the data instruments for this research are humans themselves, meaning that researchers first need to fully understand the situation in this research. The research results show that the role of the Luwu Regency Environmental Service in controlling environmental damage is to make efforts to encourage and socialize the community so that they always comply with applicable regulations related to mining business permits and the factors that hinder the control of environmental damage are the lack of public awareness in maintaining environmental sustainability and also the lack of funds at the Environmental Service and the lack of field transportation equipment. Keywords: Role, Environmental Service, Environmental Damage, Illegal Mining.